RESTRUKTURISASI SEMI PUBLIK SEBAGAI PENERAPAN ASAS ITIKAD BAIK DAN ASAS KELANGSUNGAN USAHA DI TENGAH KEPAILITAN PERUSAHAAN GO-PUBLIC DI INDONESIA - Kurniawan, Itok; Sialagan, Sahat Poltak; Fernandes, Acacio (Wacana Hukum, 2024)
Various problems related to the effectiveness and efficiency of legal proceedings are still found in the running of insolvency law in Indonesia, such as peace issues. Whereas peace is the key for companies to keep going, including for companies going public. Therefore, might consider new concepts in the Insolvency Law, such as semi-public restructuring. The purpose of this study is to find out the insolvency and PKPU proceedings and their problems in Indonesia and dissect the concept of semi-public restructuring to be a consideration for future legal development. This research uses a normative juridical approach method which is carried out by collecting data and prioritizing legal research as the source. This research shows that semi-public restructuring presents a more flexible restructuring concept so as to strengthen the extension of the principle of good faith and the principle of business continuity